TEACHERS' STRATEGIES FOR STUDENTS’ CONFIDENCE IN SPEAKING ENGLISH IN THE POST-PANDEMIC ERA - Nidara, Eris; Priajana, Nana (Universitas Bunda Mulia, 2024)
Speaking is one of the most important skills that students must have, but every studenthas a different capability to speak English. After COVID-19, there have been many changes;the learning system that was previously online has returned to being offline. This study aimsto find out the strategies the teacher used for students’ self-confidence in speaking English atjunior high school in Cirebon. It was carried out to gather data on the reasons why studentshave difficulty speaking in the post-pandemic era as well as the methods teachers use to teachspeaking to help students gain more confidence speaking English. Three methods ofgathering data were used in this study's qualitative research design, which is presented as acase study: observation, interview, and documentation. Three English teachers were thesubjects of this study. The information acquired from classroom observations wassupplemented with data from interviews. All of the data were analyzed using three majorphases of analysis: data reduction, data display, and conclusion drawing and verification. Theresults of this study revealed there are four strategies that used by teacher for studentsconfidence in speaking English after pandemic era, these strategies are Discussion, Role-play,Picture Describing, and Modelling. The researchers found problems experienced by studentsin learning English speaking after the pandemic, there are lack of vocabulary, lack ofawareness to learn, lack of practice, and gadget addiction. The researcher also found ways forteachers to overcome problems experienced by students, including giving motivation, givingappreciation, using interesting teaching strategies, taking an emotional approach to students,and the last is giving additional time.Keywords: Teachers Strategies, Speaking Skill, Students Confidence, Post-Pandemic